PHYSICIAN PERFORMANCE ANALYSIS BASED ON INDIVIDUAL, PSYCHOLOGICAL AND ORGANIZATIONAL FACTORS IN MEDICAL RESUME FILLING - mirfat, sayyidah; azzuhri, misbahuddin; hakim, lukman (Jurnal Aplikasi Manajemen, 2018)
This study aims to determine the influence of Individual, psychological and organizational factors on the performance of physicians in the medical resume completeness.The research design is observational research with a cross sectional approach. The population of this study is all physician who becomes a doctor in charge of serviceand medical resume documents that are the responsibility of the physician. The instrument in this study was a questionnaire given to the physician. Partial Least Square (PLS) was used as data analysis method.The results showed that 34.4% of respondents had complete medical resume <50%. Also, some doctors did not know the importance of a medical resume in National Health Insuranceera. Psychological factor has the most significant direct effect coefficient on physician performance with immediate effect coefficient of 0.334.The conclusion of this studyare the Individual factors had a negative but not significant effect on physician performance,psychological factors have a negative and significant impact on physician's performance,and organizational factors have a positive but not significant impact on physician performance. The hospital should facilitate a gathering event for doctors and facilities for external training for doctors can be awarded as rewards to the best performing physician.